E-BUSINESS TO SUPPORT SALES OF FARMER CROPS BASED ON MOBILE APPLICATIONS - Muhammad Aiman Abdul Hafizh; Ari Purno Wahyu Wibowo (JURNAL DARMA AGUNG, 2023)
The agricultural sector is essential because it is the leading sector and supports the Indonesian economy. Sukapura Village is one of the producers of plant products in the Kertasari District. But on the other hand, most of the farmers experienced problems, and several obstacles emerged, such as the accumulation of harvests that were sold at low prices, which resulted in losses, and the difficulty of distribution because it was pretty complicated. Of course, this situation must be improved so that people can enjoy Indonesian agricultural products. One of them is by building an android-based application "Petani Sejahtera" which is specifically made as an alternative to make it easier for farmers. It can break the distribution chain of agricultural products. You can directly contact the courier who has collaborated with the manager by displaying information on product price lists, farmers' products, and harvested products, which will later be distributed during the main harvest period. So that later, farmers will find it easier to see the products planted and do not have to think about how to distribute the products. The purpose of making this "Petani Sejahtera" Application is to help farmers more easily distribute their products to various suppliers, so there is no accumulation of harvest yields. The benefits generated have a positive influence, especially regarding the price of products produced by farmers following the "current" market price so that farmers do not experience losses and continue to increase their agricultural output.